Effect of transverse distribution profile of thulium on the performance of thulium-doped fibre amplifiers - Emami, Siamak Dawazdah; Abdul-Rashid, Hairul Azhar; Ahmad, Harith; Ahmadi, A.; Harun, Sulaiman Wadi (Institute of Physical Optics, 2012)
We study numerical models for different transverse thulium distribution profiles (TTDPs) characterising the fibres used in thulium-doped fibre amplifiers (TDFAs). Our models consider the overlap factor and the absorption/emission dynamics. Basing on the radial TTDP function of the form nT (r) = nT,max exp[-(| r-δ |/θ) β], we show that the TDFA gain increases with increasing β parameter and decreases as the θ parameter increases from 1 up to 3 μm, due to the overlap factor which affects the absorption and emission dynamics of the TDFA. The overlap factor increases with increasing β and decreases with increasing θ value. Finally, the noise figure increases as θ does so, due to suppression of the amplified spontaneous emission.